Selenoprotein: Potential Player in Redox Regulation in Chlamydomonas reinhardtii - Sandip A. Ghuge; Ulhas Sopanrao Kadam; Jong Chan Hong (Antioxidants, 2022)
Selenium (Se) is an essential micro-element for many organisms, including Chlamydomonas reinhardtii, and is required in trace amounts. It is obtained from the 21st amino acid selenocysteine (Sec, U), genetically encoded by the UGA codon. Proteins containing Sec are known as selenoproteins. In eukaryotes, selenoproteins are present in animals and algae, whereas fungi and higher plants lack them. The human genome contains 25 selenoproteins, most of which are involved in antioxidant defense activity, redox regulation, and redox signaling. In algae, 42 selenoprotein families were identified using various bioinformatics approaches, out of which C. reinhardtii is known to have 10 selenoprotein genes. However, the role of selenoproteins in Chlamydomonas is yet to be reported. Chlamydomonas selenoproteins contain conserved domains such as CVNVGC and GCUG, in the case of thioredoxin reductase, and CXXU in other selenoproteins. Interestingly, Sec amino acid residue is present in a catalytically active domain in Chlamydomonas selenoproteins, similar to human selenoproteins. Based on catalytical active sites and conserved domains present in Chlamydomonas selenoproteins, we suggest that Chlamydomonas selenoproteins could have a role in redox regulation and defense by acting as antioxidants in various physiological conditions.